2013
DOI: 10.4161/cc.26987
|View full text |Cite|
|
Sign up to set email alerts
|

DDB2 association with PCNA is required for its degradation after UV-induced DNA damage

Abstract: (2014) DDB2 association with PCNA is required for its degradation after UV-induced DNA damage, Cell Cycle, 13:2, 240-248,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 45 publications
4
24
0
Order By: Relevance
“…Our results show that DDB2 removal from damage sites is initiated following recruitment of PCNA and CRL4 Cdt2 subunits, which is consistent with PCNA-dependent proteolysis of DDB2 (Cazzalini et al, 2014;El-Mahdy et al, 2006) by CRL4 Cdt2 (Figure S6B). In addition, significant delay in PCNA and mCUL4A recruitment by PARPi substantially slows down DDB2 removal without any influence on its recruitment ( Figures S6B and S6G).…”
Section: Independent Recruitment Of Ddb1 From Ddb2supporting
confidence: 85%
“…Our results show that DDB2 removal from damage sites is initiated following recruitment of PCNA and CRL4 Cdt2 subunits, which is consistent with PCNA-dependent proteolysis of DDB2 (Cazzalini et al, 2014;El-Mahdy et al, 2006) by CRL4 Cdt2 (Figure S6B). In addition, significant delay in PCNA and mCUL4A recruitment by PARPi substantially slows down DDB2 removal without any influence on its recruitment ( Figures S6B and S6G).…”
Section: Independent Recruitment Of Ddb1 From Ddb2supporting
confidence: 85%
“…After 24 hours of pretreatment with flavonoids, HDBECs seeded on coverslips, were UV‐irradiated and fixed in methanol overnight at −20°C, then processed for CPDs or γ‐H 2 AX, respectively. Immunofluorescence stainings were performed as previously described . Photomicrographs of immunostained cells were taken with Nikon Eclipse E 400 fluorescence microscope equipped with a Canon Power Shot A590 IS digital camera.…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescence stainings were performed as previously described. [23,24] Photomicrographs of immunostained cells were taken with Nikon Eclipse E 400 fluorescence microscope equipped with a Canon Power Shot A590 IS digital camera.…”
Section: Dna Damage and Repairmentioning
confidence: 99%
“…However, there is no evidence that plant PCNA is also associated with DDB1-CUL4 complex or involved in NER process. The previous investigations in mammal cells and yeast uncovered that PCNA provides a platform and its interaction with E3 ligases CRL4 DDB2 [25] and CRL4 CDT2 [5,28] is required for the recognition of UV-induced damage DNA and subsequent DNA repair process. Our results indicated that the association between DDB1-CUL4 complex and PCNA is also conserved in plant cells.…”
Section: Discussionmentioning
confidence: 99%
“…The sequence alignment between DDI2 (SlPCNA) and the homologues from other species ( Fig. 2A) indicated that DDI2 contains all of functionally conserved features [24] (such as residue D41, motif I, motif II, motif III and an interdomain connector loop) which are responsible for proper protein folding and protein interaction [24,25]. Moreover, amino acid alignment analysis of DDI2 with tobacco PCNA2 (accession: AAD19905.1), Arabidopsis thaliana PCNA1 (accession: NP 172217), A. thaliana PCNA2 (accession: NP 180517.1) and human PCNA (accession: NP 002583.1) also demonstrated an identity of 94.5%, 90.91%, 90.94%, and 65.15%, respectively.…”
Section: Ddi2 Encodes Tomato Proliferating Cell Nuclear Antigenmentioning
confidence: 99%